A Novel Control System for Medium-Voltage Hexverter-Based Drives - Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2020)
In this paper, a novel control system for the Hexverter-based drive is proposed and analysed. Unlike previously proposed control schemes, the proposed one does not require the information of the machine variables to regulate the converter floating capacitors, as required in high-performance drive applications. The feasibility of the proposed control system is demonstrated by using simulation results of an Hexverter-based drive driving a medium-voltage machine, including the whole frequency range and high starting torque loads. © 2020 IEEE.